PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP BERPIKIR KRITIS DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA KELAS V SEKOLAH DASAR - Paradila, Niken Ayu; Hakim, Lukman; Lefudin, Lefudin (STKIP Persada Khatulistiwa Sintang, 2024)
This study aims to describe the effect of the problem based learning model on critical thinking and student learning outcomes on science subjects for grade V. The method used is a quasi-experiment with nonequivalent control group design. The population is grade V students of SD Negeri 195 Palembang, with the sample in this study were class VC with 28 students as the control class, while class VA with 27 students as the experimental class. Data collection techniques used in this research activity are tests and documentation. The data analysis technique used is the paired simple t-test. In the pretest-posttest results of the control class and the experimental class which showed a significant difference after applying the problem based learning model, the data analysis obtained was 0.000 <0.05 then H0 was rejected and Ha was accepted. After conducting the test, it can be concluded that there is a significant influence on the application of the problem based learning model on critical thinking and student learning outcomes on science subjects for grade V of elementary school.